Fear Of Missing Out (FOMO) Konsumerisme Remaja Pengguna Platform TikTok di Kelurahan Kalabbirang, Kabupaten Takalar - Juliati; Andi Ima; Muh (Indonesian Journal Publisher, 2025)
This study discusses how Fear Of Missing Out (FOMO) consumerism occurs in Teenage TikTok users in Kalabbirang Village, Takalar Regency, as a social, psychological, and digital cultural phenomenon that not only reflects the fear of being left behind, but also shapes the consumption behavior and lifestyle of teenagers in Kalabbirang Village. This study aims to identify Fear Of Missing Out (FOMO) and analyze the determinants of Fear of Missing Out (FOMO) in the consumerism behavior of teenagers using the TikTok platform in Kalabbirang Village, Takalar Regency. To achieve this goal, this study was carried out using a descriptive qualitative method with a phenomenological approach. Data collection was carried out through observation, interviews, and documentation, with informants who are active teenagers using TikTok in Kalabbirang Village with an age range of 15-19 years, as well as several parents of informants as additional data. The results of the study show that (1) Fear Of Missing Out (FOMO) consumerism of adolescent TikTok users in Kalabbirang Village is a social, psychological, and digital cultural phenomenon that shapes adolescent consumption behavior and lifestyle that appears in the form of fear of being left behind by trends, anxiety about not following recommendations from influencers and friends, and the urge to own viral goods, which are then manifested through impulsive purchases, increased spending, and dependence on product recommendation content, ultimately forming a consumptive lifestyle to show self-existence and social connectedness (2) Fear Of Missing Out (FOMO) consumerism of adolescent TikTok users in Kalabbirang Village is formed from internal factors in the form of searching for identity, self-confidence, and the need for social recognition, as well as external factors such as the influence of influencers, peer pressure, TikTok Shop features, and the socio-economic environment. Keywords: Fear Of Missing Out (FOMO), Consumerism, Teenagers, TikTok